Green Production of Cladribine by Using Immobilized 20-Deoxyribosyltransferase from Lactobacillus delbrueckii Stabilized through a Double Covalent/Entrapment Technology - Rivero, Cintia Wanda (2021)
Nowadays, enzyme-mediated processes offer an eco-friendly and efficient alternative to the traditional multistep and environmentally harmful chemical processes. Herein we report the enzymatic synthesis of cladribine by a novel 20-deoxyribosyltransferase (NDT)-based combined biocatalyst. To this end, Lactobacillus delbrueckii NDT (LdNDT) was successfully immobilized through a two-step immobilization methodology, including a covalent immobilization onto glutaraldehydeactivated biomimetic silica nanoparticles followed by biocatalyst entrapment in calcium alginate. The resulting immobilized derivative, SiGPEI 25000-LdNDT-Alg, displayed 98% retained activity and was shown to be active and stable in a broad range of pH (5–9) and temperature (30–60 C), but also displayed an extremely high reusability (up to 2100 reuses without negligible loss of activity) in the enzymatic production of cladribine. Finally, as a proof of concept, SiGPEI 25000-LdNDT-Alg was successfully employed in the green production of cladribine at mg scale.